EFEKTIVITAS PERAN BAPPEDA DALAM PERENCANAAN PEMBANGUNAN INFRASTRUKTUR DI PASAR SORE TAPIOKA KELURAHAN SIRIWINI DISTRIK NABIRE KABUPATEN NABIRE PROVINSI PAPUA - Mulyana Mulyana; Manuel Pieter Stenly Arfayan (Jurnal Ilmiah Wahana Bhakti Praja, 2021)
Pasar Sore Tapioka is a sector of the economy that has bad physical or infrastructure conditions. Building conditions like this make people need a touch from the government to build the market. This study aims to describe and analyze the effectiveness of Bappeda's role in planning infrastructure development in the Sore Tapioca Market, Siriwini Village, Nabire District, Nabire Regency. This study used descriptive qualitative method. Data was collected through interviews, observation, documentation. The selection of informants was based on a purposive sampling technique. The results of the study indicate that the Effectiveness of the Role of Bappeda in Development Planning has not been effective. In accordance with the indicators of effectiveness theory, where coordination between relevant stakeholders is still not maximized to carry out development at the Tapioca Afternoon Market. Then, the economic community is also not satisfied with the inadequate development of the market, this is because the Tapioca Afternoon Market does not yet have clear technical data or land certificates. This certificate is the basis for implementing development planning and the development of the Tapioca Afternoon Market because it will use the state budget. For this reason, the construction and development of Infrastructure at the Tapioca Afternoon Market should be carried out, as well as updating the data on land ownership of community members needs to be enforced. Thus, orderly land administration is the main capital in the success of infrastructure development at the Tapioca AfternoonMarket. Keywords: Effectiveness, Development Planning, Role of Bappeda, Sustainable Development, NabireDistrict